Shoot to win training for the new pistol, rifle, and shotgun shooter - Cheng, Chris (Skyhorse Publishing, 2018)
Learn tactics and techniques of basic marksmanship. An excellent guide for beginning shooters, focuses on the basics and ammunition of pistols, rifles, and shotguns, marksmanship fundamentals, and buy a firearm.